Обгрунтування задач дослідження торсіонних валів систем підресорювання легких броньованих машин за критеріями міцності та довговічності - Зінченко, Олена Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
В роботі показана необхідність удосконалення торсіонних валів систем підресорювання легких броньованих машин з метою поліпшення їх основних характеристик. У результаті проведення аналізу існуючих методів та методик розрахунку торсіонних валів прийшли до висновку про необхідність створення адекватної моделі, яка би включала в себе оцінку напружено-деформованого стану торсіонного валу у різних зонах із врахуванням безлічі факторів.

The paper shows the necessity of improving the torsion shafts of the suspension systems of light armored vehicles in order to improve their main characteristics. As a result of the analysis of the existing methods and methodologies of torsion shafts calculation, we came to the conclusion about the need to create an adequate model, which would include an assessment of the stress-strain state of the torsion shaft in different zones, taking into account many factors. Known simplified methods for calculating the stress-strain state of torsion shafts are not suitable for the complex nonhomogeneous components distribution of the stress-strain state and are a source of potential errors. Therefore, there is a need to apply the incremental flow theory, taking into account the load history of the torsion shaft material. In the work, it is proposed to reduce the problem to a sequence of problems with the breakdown of the load history into separate steps and within each step to simultaneously take into account the elastic-plastic deformation and contact interaction and their relationship and mutual influence. The necessity of generalized parametric modeling of the torsion shaft is shown, according to which the generalized parameters represent a set of distributions, functions, dependencies, structures, forms, properties, etc., which uniquely identify the torsion shaft. At the same time, this method makes it possible to purposefully change the current technical solution. All these studies will provide an opportunity to substantiate the parameters of torsion shafts in the context of improving their strength and durability.
Justification of the problems of research of torsion shafts of suspension systems of light armored vehicles according to strength and durability criteria
Keywords: підвіска; системи підресорювання; легка броньована машина; торсіонний вал; тактико-технічні характеристики; транспортні засоби спеціального призначення; головка торсіонного вала; стебло торсіонного вала; галтельний перехід; узагальнене параметричне моделювання; suspension; suspension systems; light armored vehicle; torsion shaft; tactical and technical characteristics; special purpose vehicles; torsion shaft head; torsion shaft stem; halyard transition; generalized parametric modeling